2013
DOI: 10.3389/fpsyg.2013.00595
|View full text |Cite
|
Sign up to set email alerts
|

Separating acoustic deviance from novelty during the first year of life: a review of event-related potential evidence

Abstract: Orienting to salient events in the environment is a first step in the development of attention in young infants. Electrophysiological studies have indicated that in newborns and young infants, sounds with widely distributed spectral energy, such as noise and various environmental sounds, as well as sounds widely deviating from their context elicit an event-related potential (ERP) similar to the adult P3a response. We discuss how the maturation of event-related potentials parallels the process of the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 178 publications
11
91
0
Order By: Relevance
“…In contrast, ILD and ear of stimulation deviants elicited negative differential responses of more central scalp 13 distribution in the same latency range. The latter polarity and scalp distribution is similar to the early negativity observed by several previous ERP studies in neonates for spectrally rich deviant sounds (Kushnerenko et al 2007(Kushnerenko et al , 2013. Therefore, although Bundy (1980) found no evidence for sensitivity to change in ILD until 16 weeks of age as measured with a visual fixation paradigm, we can conclude that the neonatal auditory cortex is sensitive to deviation in ILD and the ear of stimulation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast, ILD and ear of stimulation deviants elicited negative differential responses of more central scalp 13 distribution in the same latency range. The latter polarity and scalp distribution is similar to the early negativity observed by several previous ERP studies in neonates for spectrally rich deviant sounds (Kushnerenko et al 2007(Kushnerenko et al , 2013. Therefore, although Bundy (1980) found no evidence for sensitivity to change in ILD until 16 weeks of age as measured with a visual fixation paradigm, we can conclude that the neonatal auditory cortex is sensitive to deviation in ILD and the ear of stimulation.…”
Section: Discussionsupporting
confidence: 87%
“…However, FF deviants elicited a robust positive difference response in the 290-340 ms latency range. This response is similar to the "central positivity" described in many previous ERP studies of neonatal sound discrimination (Kushnerenko et al 2007(Kushnerenko et al , 2013). Thus we conclude that the newborn brain encodes changes in sound source location.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Th ese results added to the existing literature by showing that there are active neural mechanisms for mismatch detection in the infant brain not only for subsequent stimuli in the auditory modality (see Kushnerenko, Van den Bergh, & Winkler, 2013), but also for bimodal audiovisual stimuli. Originally, Kushnerenko et al (2008) suggested that this early capacity for detecting mismatch between auditory and visual speech information is a signature of an important neural mechanism that may assist infants' learning about native speech sounds.…”
Section: Attention To Av Mismatch Is Associated With the Neural Mismamentioning
confidence: 64%
“…Although this suggests an early developmental time course for the processing of concurrent cues, one cannot infer that the capacity is innate given the widespread changes that auditory processing undergoes between birth and 6 months of age [11,12,13,14]. Fortunately, concurrent sound segregation can be measured not only behaviorally (which would be difficult in neonates) but also by electrophysiological methods.…”
Section: Introductionmentioning
confidence: 99%